Penanaman Karakter Disiplin melalui Pengenalan Rambu-Rambu Lalu Lintas pada Anak Usia Dini di TK Islam Al-Anshor Palembang - Sinta Sri Wulandari; Muhtarom, Muhtarom; Nyimas Atika; Yecha Febrieanitha Putri; Maryamah, Maryamah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Discipline character education in early childhood refers to instilling obedience to rules at home, school, and in society for children aged 0–6 years. This education serves as a crucial foundation for shaping future generations. This study aims to examine the implementation of traffic ethics education for young children, the strategies used, and influencing factors at Al-Anshor Islamic Kindergarten Palembang in the 2023/2024 Academic Year. A qualitative descriptive method was employed, involving two teachers (Class A and B) as the main data sources. Data were collected through observation, interviews, and documentation. The findings reveal that the strategy for teaching traffic ethics includes: (1) Planning, by integrating traffic ethics indicators into RKM and RPPH; (2) Implementation, through integration in learning activities, school culture, and daily routines; and (3) Evaluation, conducted in conjunction with other learning assessments. The character values fostered through this process include self-confidence, discipline, and responsibility. These findings suggest that incorporating traffic ethics education into early childhood learning can effectively instill discipline, contributing positively to children's character development and awareness of civic responsibility from an early age.